A Novel Radio-Over-Fiber System Based on Carrier Suppressed Frequency Eightfold Millimeter Wave Generation - Huizhong Zhang; Lin Cai; Shuixian Xie; Kaiming Zhang; Xinxing Wu; Ze Dong (IEEE Photonics Journal)
We propose a novel and simple scheme for photonic frequency eightfold millimeter wave (mm-wave) generation with optical carrier suppression based on only one single-drive Mach–Zehnder modulator (MZM). According to our theoretical analysis and experimental demonstration, by adopting designed direct current bias voltage of MZM and the amplitude voltage of the radio frequency (RF) drive signal, two fourth-order optical subcarriers are generated via a single-drive MZM. Furthermore, the corresponding optical central carrier and undesired sidebands are suppressed simultaneously. Based on our proposed scheme, the generation of 72-GHz optical mm-wave by an RF signal of 9 GHz without any optical filtering is experimentally demonstrated. The radio-over-fiber system with 3.5-Gb/s OOK downstream link based on this generated 72-GHz mm-wave is also experimentally demonstrated. As we know, it is the first time to realize frequency eightfold mm-wave signal generation with simultaneous carrier suppression by using only one single-drive MZM in experiment.